A Review on Artificial Intelligence and The Education of Gifted Learners in Inclusive Settings - Bala , MaryamYahaya; Abubakar, Aishatu Tongo; Abdullahi , Auwalu Salihu (Kashere Journal of Education, 2025)
The rapid advancement of artificial intelligence (AI) has significantly transformed contemporary educational systems by enabling personalised learning, increasing instructional efficiency, and expanding access to rich learning opportunities. This paper examines the role of AI in enhancing the education of gifted learners in inclusive settings, where individualised learning needs often vary widely. This study looks at how AI tools like adaptive learning systems, intelligent tutoring systems, machine-learning identification models, and automated assessment technologies help gifted students grow in their thinking, social skills, and academics. AI facilitates differentiated instruction by adapting content to learners’ abilities, offering real-time feedback, and enabling self-paced progression. It also broadens access to advanced learning for gifted students in underserved or remote areas, while easing teachers’ administrative workloads and improving instructional quality. Despite these benefits, the paper highlights persistent challenges, including overreliance on technology, ethical concerns, data privacy risks, digital inequities, and gaps in teacher preparedness. The findings emphasise that, while AI holds strong potential to revolutionise gifted education in inclusive classrooms, its successful implementation requires ethical design, equitable access, informed pedagogical integration, and ongoing teacher training. The paper concludes that AI, when thoughtfully deployed, can create enriched, responsive, and empowering learning environments where gifted learners thrive academically, socially, and emotionally alongside their peers.